Calculation of energy release rate for adhesive composite/metal joints under mode-I loading considering effect of the non-uniformity. (15th June 2016) - Jiang, Zhengwen; Wan, Shui; Wu, Zhishen
Abstract: A simplified plate model based on Kirchhoff theory is proposed for the un-symmetric double cantilever specimens (DCB) under pure mode-I loading. Based on the results of three-dimension finite element analysis, the calculation for non-uniformity coefficients βB of composite/metal DCB specimen can be converted to determination of non-uniformity coefficients βG, βS for two symmetric DCB specimens composed of composite laminates and metal plate, respectively. Using Kantorovich method and virtual crack closure technique (VCCT), βG, βS for the symmetric DCB specimens can be obtained. Then, energy release rate (ERR) considering influence of the non-uniformity can be determined conveniently using theoretical solution for βB combined with Timoshenko beam theory and the adhesive model of Goland and Reissner. The accuracy of theoretical solution is validated by the comparisons with transverse deformations and ERR distribution for the symmetric DCB specimens, non-uniformity coefficients βG, βS, βB and maximum ERR of the un-symmetric DCB specimens determined using the finite element method.